Investigação do processo oxidativo avançado (UV/H2O2/carvão ativado) no tratamento de efluentes industriais: eliminação de fenol - Martins, Michelly Freitas de Moraes (2017)
Due to the need for more efficient technologies for the phenol elimination in effluents, the objective of this study was to evaluate the efficiency of the UV/H2O2/AC process and the adsobent behavior in the coupling to eliminate phenol. For a determination of the physical characteristics of the activated carbon, a textural analysis was carried out for isotherms of adsorption and desorption of N2 at 77 K, scanning electron microscopy, thermogravimetric analysis and differential thermal analysis. Regarding the chemical nature of the coal were carried out as techniques of infrared spectroscopy, elemental analysis, Boehm method and zero load point. Adsorption kinetics were used to determine the adsorption capacity, for each of the 11 tests, according to the experimental design 23 + 3 central points, where the pH, temperature and the quantity of carbon activated varied. The experimental data obtained in adsorption kinetics were adjusted to the kinetic models of pseudo-first order, pseudo-second order and intraparticle diffusion, with pseudo-second order being the best represent the adsorption process of all the tests. Adsorption isotherms (15, 30 and 45°C) were then adjusted, adjusting the values to the Langmuir and Freundlich models. All feared a better fit of the data to the Freundlich model. For the treatments H2O2/UV and H2O2/UV/AC a factorial design 22 + 3 central points was used, varying pH and H2O2 concentration and quantified response by rate of phenol removal. For both treatments the pH showed a negative release on elimination rate and a concentration of H2O2 showed positive effect. The best tests for H2O2/UV and H2O2/UV/AC processes were the central points (pH 7 and 20 mmol H2O2), with phenol elimination rates of 89% and 94.16%, respectively. With the presence of a free radical inhibitor (tert-butanol) the kinetic contribution of the hydroxyl radicals was calculated, showing that 77.64% of the phenol elimination in the H2O2/UV/AC treatment was caused by their action. The H2O2/UV/AC coupling process is acceptable, presenting a higher removal rate than the adsorption process with much shorter removal time.